Insertability comparison of passive bending single-balloon prototype versus standard single-balloon enteroscopy: a multicenter randomized non-blinded trial - Hosoe, Naoki; Ohtsuka, Kazuo; Endo, Yutaka; Naganuma, Makoto; Ogata, Noriyuki; Kuroki, Yuichiro; Sasanuma, Seiko; Takabayashi, Kaoru; Kudo, Shin-Ei; Takahashi, Hiroshi; Ogata, Haruhiko; Kanai, Takanori (Endoscopy International Open, 2018)
Background and study aims Traversing the ileocecal valve (ICV) is technically challenging with a retrograde approach to single-balloon enteroscopy (SBE). A novel technique called responsive insertion technology (RIT) colonoscopy was developed to obtain a higher cecal intubation rate in this setting. A prototype long SBE equipped with RIT (P-SBE) was developed to obtain superior insertability. The aim of this study was to compare the insertability of a standard single-balloon enteroscope (S-SBE) versus a P-SBE. Patients and methods This study was a multicenter, randomized, non-blinded, trial of 62 patients with small bowel pathologies. All procedures were performed with SBE via the trans-anal route. Procedure success was defined as stable intubation of the terminal ileum (TI) 20 cm beyond the ICV. The primary variable was time to reach stable TI intubation 20 cm beyond the ICV (TSTII). If stable TI intubation was not achieved within 10 minutes, the initial SBE was removed through the indwelling overtube and replaced with another SBE.Results Sixty patients were examined with two patients excluded from this study. TSTII using P-SBE was significantly decreased compared to S-SBE (mean P-SBE vs S-SBE: 98.3 vs 169.4 second, P = 0.006). The completion rates for stable intubation within 10 minutes of using P-SBE and S-SBE were 96.8 % and 86.2 %, respectively (P = 0.19). On endoscope replacement, all patients had achieved stable TI intubation.Conclusions SBE with RIT improves insertability when traversing the ileocecal valve in retrograde SBE.